Splice variant in ARX leading to loss of C‐terminal region in a boy with intellectual disability and infantile onset developmental and epileptic encephalopathy. Issue 8 (30th May 2019) - Shoubridge, Cheryl; Jackson, Matilda; Grinton, Bronwyn; Berkovic, Samuel F.; Scheffer, Ingrid E.; Huskins, Shannon; Thomas, Alison; Ware, Tyson
Abstract: Pathogenic variants in the X‐chromosome Aristaless ‐related homeobox ( ARX ) gene contribute to intellectual disability, epilepsy, and associated comorbidities in affected males. Here, we report a novel splice variant in ARX in a family with three affected individuals. The proband had early onset developmental and epileptic encephalopathy, his brother and mother had severe and mild intellectual disability, respectively. Massively parallel sequencing identified a novel c.1449‐1G>C in intron 4 of the ARX gene, predicted to abolish the splice acceptor site, retaining intron 4 and leading to a premature termination codon immediately after exon 4. As exon 5 is the last exon of the ARX gene, the premature termination codon at position p.L484* would be predicted to escape nonsense‐mediated mRNA decay, potentially producing at least some C‐terminally truncated protein. Analysis of cDNA from patient lymphoblastoid cells confirmed retention of intron 4 and loss of detectable expression of ARX mRNA across exon 4 to exon 5. We review published cases of variants that lead to altered or early termination of the ARX protein, but not complete loss of function, and are associated with phenotypes of intellectual disability and infantile onset developmental and epileptic encephalopathies, including Ohtahara and West syndromes. Taken together, this novel splice variant retaining intron 4 is likely to be the cause of the early onset developmental and epileptic encephalopathy in the proband.